2017
DOI: 10.24136/oc.v8i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selected internationally recognized brand valuation methods

Abstract: Research background: There are many consultative groups and market research companies on the market that have also brand valuation included in their service portfolios. Such companies tend to adopt their own unique approaches to value brands to face increasing competition, which is also reinforced by the fact that brand constitutes the company's most valuable commercial and intangible assets. The paper compares selected internationally recognized brand valuation methods, using the mathematical statistics appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Therefore, the more important companies' intangibles are (Bistrova et al, 2017), the more interest they will show in knowing and specifying their valuation. Nonetheless, the fact that a brand is an intangible means that its valuation is complex and often ambiguous (Janoskova & Krizanova, 2017).…”
Section: Brands and Their Valuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the more important companies' intangibles are (Bistrova et al, 2017), the more interest they will show in knowing and specifying their valuation. Nonetheless, the fact that a brand is an intangible means that its valuation is complex and often ambiguous (Janoskova & Krizanova, 2017).…”
Section: Brands and Their Valuationmentioning
confidence: 99%
“…To fulfil this objective, it is necessary to empirically demonstrate that these differences exist, and to know the degree of similarity in these consultancy companies' brand valuations. Several theoretical studies (Aaker, 1996;Salinas, 2009;Salinas & Ambler, 2009) reveal differences between brand valuation methods, but only three empirical studies about the brand values reported by these companies can be found (Alcaide et al, 2019;Bagna et al, 2017;Janoskova & Krizanova, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nagaraj & Singh (2018), Valaskova et al (2018) and Ledikwe et al (2019) note that high quality builds consumer loyalty to the brand. Janoskova & Krizanova (2017) add that "the brand name identification with consumers creates benefits that the enterprise may charge higher price for the same product, leading to higher profit margins, growth and firm value to net sales ratio". Successful differentiation of the brand products has been gained worldwide (Singh & Singla, 2018) and for the enterprises, it is necessary to know the assessment of delivered quality brand products from the view of the consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Such a specific in its very rough features is the status and perception of quality in the process of brand value building. According to previous research, there are significant discrepancies between practical implications of countries where brand is identified with quality and countries where brand is identified with image and social status [17,18,19,20].…”
Section: Literature Reviewmentioning
confidence: 99%